2020
DOI: 10.3390/cells9051084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BDNF Val66Met Polymorphism on Myocardial Infarction: Exploring the Macrophage Phenotype

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin growth factor family, well known for its role in the homeostasis of the cardiovascular system. Recently, the human BDNF Val66Met single nucleotide polymorphism has been associated with the increased propensity for arterial thrombosis related to acute myocardial infarction (AMI). Using cardiac magnetic resonance imaging and immunohistochemistry analyses, we showed that homozygous mice carrying the human BDNF Val66Met polymorphism (BDNFMet/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…On the one hand, BDNF has been reported to be increased when measured in the first hours after AMI [37], and to be associated with the severity of acute heart failure due to AMI [38]. On the other hand, reduced BDNF levels have been related to adverse cardiac remodeling after AMI [39,40]. Experimental AMI models also provided conflicting results, with some…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, BDNF has been reported to be increased when measured in the first hours after AMI [37], and to be associated with the severity of acute heart failure due to AMI [38]. On the other hand, reduced BDNF levels have been related to adverse cardiac remodeling after AMI [39,40]. Experimental AMI models also provided conflicting results, with some…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, BDNF has been reported to be increased when measured in the first hours after AMI [37], and to be associated with the severity of acute heart failure due to AMI [38]. On the other hand, reduced BDNF levels have been related to adverse cardiac remodeling after AMI [39,40]. Experimental AMI models also provided conflicting results, with some reports showing that BDNF reduces infarct size and ameliorates cardiac function [41], others showing that it increased the extent of inflammation and myocardial injury [42].…”
Section: Discussionmentioning
confidence: 99%
“…5-HT metabolic disorder inhibits the cAMP signaling pathway ( Louiset et al, 2017 ). The cAMP signaling pathway was observed in both CHD and depression patients ( Amare et al, 2017 ; Wang and Mao, 2019 ; Sandrini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages BDNF promotes the shift from pro-inflammatory to reparative polarization, thereby modifying the inflammatory microenvironment [ 97 ]. It has recently been reported that a polymorphism of BDNF (Val66Met), well known to be related to mood disorders and neurodegenerative diseases, also has an impact on the reactive state of macrophages following MI, predominantly by promoting the pro-inflammatory state, thereby predisposing to adverse cardiac remodeling [ 98 , 99 ]. Thus, neurotrophins such as BDNF influence all three regenerative phases following MI.…”
Section: Tgfβ and Neurotrophin Signaling In The Heartmentioning
confidence: 99%